COMMON ILIAC ARTERY PERFORATION CAUSED BY BLUNT TRAUMA: A CASE REPORT - (:unkn) unknown (EMERGENCY MEDICINE PHYSICIANS ASSOC TURKEY, 2020)
Introduction: Retroperitoneal hemorrhage from iliac artery injury is a potential cause hemorrhagic shock and death if not diagnosed early and treated promptly. Case Report: A 55-year-old man, who had non-penetrating blunt trauma, presented with hemorrhagic shock due to retroperitoneal hemorrhage from right common iliac artery. Although non-penetrating blunt trauma is not a common cause of iliac artery injury, this case demonstrates that deployment of a peripheral drug-eluting stent can successfully treat a common iliac artery (CIA) perforation caused by a blunt trauma. Conclusion: In this case report, we want to share our experience on the successful endovascular treatment of iliac artery perforation after a non-penetrating blunt trauma in patients with hemorrhagic shock. We indicate that this approach is a less invasive treatment modality than conventional surgical repair of iliac artery perforation.
Keywords: Common iliac artery; computed tomography; endovascular treatment; peripheral stent; non-penetrating blunt trauma; MANAGEMENT; OUTCOMES; RUPTURE; INJURY